2008
DOI: 10.1136/emj.2007.056614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deep vein thrombosis on ischaemia-modified albumin levels

Abstract: DVT is associated with raised serum IMA levels but IMA levels are not suitable as a diagnostic marker for DVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…IMA levels have also been studied in the context of pulmonary embolism and peripheral arterial disease. [3][4][5] Two recent reports found IMA to be valuable in the early diagnosis of intestinal ischemia. The first, a casecontrol study, found serum IMA levels (measured using the same rapid colorimetric, albumin-cobalt binding test as we used in our study) to be significantly higher (0.26 ± 0.06 ABSU) in patients with mesenteric ischemia than in those of the control group (0.16 ± 0.02 ABSU).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IMA levels have also been studied in the context of pulmonary embolism and peripheral arterial disease. [3][4][5] Two recent reports found IMA to be valuable in the early diagnosis of intestinal ischemia. The first, a casecontrol study, found serum IMA levels (measured using the same rapid colorimetric, albumin-cobalt binding test as we used in our study) to be significantly higher (0.26 ± 0.06 ABSU) in patients with mesenteric ischemia than in those of the control group (0.16 ± 0.02 ABSU).…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia-modified albumin (IMA) is a relatively recently described marker that measures cobalt binding to albumin and has been suggested as a valuable tool in the early diagnosis of a variety of ischemic conditions, such as acute myocardial ischemia, pulmonary embolism, and peripheral arterial disease. [3][4][5] Doppler ultrasonography, spiral computed tomography, and mesenteric angiography are commonly used imaging modalities for diagnosing mesenteric ischemia. [6][7][8] These can be invasive, costly, viewer-dependent, and time-consuming.…”
mentioning
confidence: 99%
“…IMA, which appears to be an indicator of oxidative stress, may not be specific for cardiac ischemia. Studies have demonstrated that many conditions may elevate IMA levels, such as mesenteric ischemia, peripheral arterial occlusion, deep venous thrombosis, stroke and acute cardiac arrest, and that IMA may be a diagnostic biomarker for these conditions (21)(22)(23)(24)(25). There are only a few reports in the literature about the diagnostic value of IMA in the diagnosis of PE.…”
Section: Discussionmentioning
confidence: 99%
“…DVT is believed to be a multifactorial disease that occurs (IMA) levels in a DVT group compared with a control group [23]. IMA, a Food and Drug Administration-approved serum biomarker of cardiac ischemia, appears to be an indicator of oxidative stress and may not be specific for cardiac ischemia [24].…”
Section: Discussionmentioning
confidence: 99%